2020
DOI: 10.1111/grs.12270
|View full text |Cite
|
Sign up to set email alerts
|

Climatic suitability mapping and driving factors detection for whole crop maize and sorghum–sudangrass hybrid production in the south area of the Korean Peninsula and Jeju Island

Abstract: The climatic suitability and driving climatic factors of forage crops are considered fluctuant, and their measurements are important for the production of high-quality forage under the context of global climate change. Meanwhile, need for improving the domestic supply of high-quality forage sources is increasing in the related parties of forage and livestock production in Korea. Therefore, this study analyzed the climatic suitability conditions of whole crop maize (Zea mays L.) and sorghum-sudangrass hybrid (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Therefore, it has broad application prospects in environmental protection, animal husbandry, and aquaculture, among others. It is widely planted in the United States [ 2 ], including northern Colorado [ 3 ], China [ 4 ], the southern part of the Korean Peninsula, and most of the dry areas of Jeju Island [ 5 ]. Dong et al [ 6 ] reported that the sorghum-sudangrass hybrid is rich in amino acids, sugars, minerals, and other compounds, with high nutritional value and good palatability, and is commonly used as hay, silage, or green feed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has broad application prospects in environmental protection, animal husbandry, and aquaculture, among others. It is widely planted in the United States [ 2 ], including northern Colorado [ 3 ], China [ 4 ], the southern part of the Korean Peninsula, and most of the dry areas of Jeju Island [ 5 ]. Dong et al [ 6 ] reported that the sorghum-sudangrass hybrid is rich in amino acids, sugars, minerals, and other compounds, with high nutritional value and good palatability, and is commonly used as hay, silage, or green feed.…”
Section: Introductionmentioning
confidence: 99%
“…An insufficient forage supply has become a limiting factor in the livestock industry in the northwestern Himalayan region of India [ 7 ], the southern part of the Korean Peninsula and Jeju Island [ 5 ], the northern and southeastern United States [ 8 , 9 ], and China [ 10 ]. Therefore, it is necessary to identify key genes that control desirable traits and select new varieties of the sorghum-sudangrass hybrid with high yields and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle, sheep, geese, ducks, poultry, and other livestock utilize this hybrid as feed. The sorghum-sudangrass hybrid presents a developed root system, good soil capacity, and strong ecological adaptability and further presents broad development and utilization prospects in environmental protection and animal husbandry, especially the development of the breeding industry in agricultural areas ( Saballos et al., 2008 ; Han et al., 2015 ; Mahmoudzadeh and Oad, 2018 ; Peng et al., 2020 ). In recent years, with the rapid development of animal husbandry and frequent extreme weather worldwide, increasing demand for high-quality forage has indicated a shortage of high-quality green and fresh forage.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of animal husbandry and frequent extreme weather worldwide, increasing demand for high-quality forage has indicated a shortage of high-quality green and fresh forage. This is the main reason for limiting the quality and efficiency of animal husbandry in the northwestern Himalayan region of India ( Mir et al., 2020 ; Kumar et al., 2022 ), the southern part of the Korean Peninsula and Jeju Island ( Peng et al., 2020 ), the northern and southeastern United States ( Wells et al., 2014 ; Nave et al., 2020 ), northern Europe ( Liatukienė et al., 2008 ), Canada ( Bélanger et al., 2006 ), and parts of China ( Fang, 2018 ). Therefore, increasing forage yield is crucial in meeting sufficient livestock nutrition and accelerating production.…”
Section: Introductionmentioning
confidence: 99%
“…For Dillard et al (2017) in temperate countries these hybrids are good alternatives for summer pastures production when winter forages have low productivity. In regions with low rainfall, planting in summer allows good forage accumulation in short time period (Peng et al 2020).…”
Section: Introductionmentioning
confidence: 99%